Implications of Education and Training on Lecturers' Knowledge of OSCE Exam Planninganaan Ujian OSCE - Nuryati Nuryati; Nova Oktavia (Gayaku Publisher, 2026)
Background: The Objective Structured Clinical Examination (OSCE) is a standardized assessment method used to evaluate the clinical competence of medical and health science students, ensuring they are capable of performing professional tasks according to established standards. However, not all health education institutions have implemented OSCE due to limited infrastructure, facilities, and human resources. Objective: To determine the relationship between education and training and lecturers' knowledge regarding OSCE examination planning. Methods: This study employed an analytical observational design with a cross-sectional approach. The study population consisted of lecturers from the Diploma III Medical Record and Health Information and Diploma IV Health Information Management Study Programs in Regional Coordinators I–XI. A total of 117 lecturers were recruited using a total sampling technique. The independent variable was education and training, while the dependent variable was lecturers' knowledge of OSCE examination planning. Data were collected using a structured questionnaire and analyzed through univariate and bivariate statistical analyses. Results: The findings revealed a statistically significant relationship between education and training and lecturers' knowledge of OSCE examination planning. Lecturers who had participated in education and training demonstrated better knowledge regarding the preparation and implementation of OSCE examinations than those who had not received such training.Conclusion: Education and training significantly improve lecturers' knowledge of OSCE examination planning. Strengthening lecturers' competencies through continuous professional development is essential to support the effective implementation of standardized OSCE assessments in health education institutions. Suggestion: Health education institutions should collaborate with professional medical record organizations and OSCE experts to develop standardized OSCE examination materials. In addition, institutions should invest in adequate facilities, infrastructure, and human resources to ensure the successful implementation of OSCE examinations and improve the quality of competency-based assessment.